Gut microbiota changes and biological mechanism in hepatocellular carcinoma after transarterial chemoembolization treatment - Bian, Chao-fan; Wang, Ying; Yu, Ao; Fu, Lulan; Zhang, Ding; Zhu, Wenzhi; Lv, Weifu (Frontiers in Oncology, 2022)
Background and aims Intestinal flora is closely associated with the occurrence and development of hepatocellular carcinoma (HCC). However, gut microbial changes and biological mechanisms in HCC after transarterial chemoembolization (TACE) treatment are rarely reported. Methods We evaluated changes in intestinal flora after TACE in rabbit HCC models and assessed the impact of these changes on the disease. Twenty-four rabbit VX2 HCC models were established and intestinal flora structures, intestinal barrier function, changes in blood lipopolysaccharide (LPS) levels, Toll-like receptor 4 (TLR4), Cyclooxygenase-2 (COX-2), and p-signal transducer and activator of transcription 3(p-STAT3) protein expression levels were studied after TACE treatment. Results Compared with healthy rabbits, the intestinal flora in HCC models exhibited structural changes; intestinal barrier function was decreased, and increased LPS levels entered the circulation. A short-term follow-up after TACE showed the procedure partially reversed the intestinal microflora disorder caused by the tumor: intestinal barrier and liver functions were improved, intestinal LPS levels in the blood were reduced, and liver metabolism toward LPS was enhanced. Correlation analyses of the first 75 significantly changed bacteria with clinical factors showed that harmful bacteria had decreased and beneficial bacteria increased. Blood LPS levels and downstream signaling molecule TLR4, COX-2, and p-STAT3 protein expression levels were reduced, which correlated with tumor drug resistance and invasion capabilities. Conclusions We first characterized gut microbiota changes and biological mechanisms in HCC after TACE treatment. Our data provide a theoretical research basis for TACE combined with an intestinal flora intervention and systemic chemotherapy.